KNOWLEDGE MANAGEMENT AND JOB SATISFACTION IN THE CIVILITY OF THE FACULTY OF TARBIYAH AND TEACHER, STATE ISLAMIC UNIVERSITY OF MATARAM - Al Idrus, S. Ali Jadid (Universitas Islam Negeri Mataram, 2022)
This paper aims to explore the role of knowledge management on employee satisfaction, and explore the ability to strengthen knowledge management professional relationships with faculty strategies and innovation-based continuous learning processes. A qualitative method with a case study approach is used in examining the focus of the problem, the researcher is the key research instrument using a qualitative method with a case study type. Data were collected through observation techniques, interviews, and documentation with data analysis through an interactive approach. Legitimacy with standards of credibility, conformability, transferability, and dependability. The results of this study are (1) The challenges of working mentally show that civility can use their skills and abilities; (2) Experienced, moderate, and have the sensitivity to develop themselves; (3) Rewards are balanced, related to the system of rewards and promotions based on job requests, individual skill levels, a set of standards that apply to the end of the work environment, then satisfaction will seek wisdom; and (4) Supporting working conditions, so that workers can work well.